“Kenapa Duniaku Begitu Melelahkan?”: Mengungkap Parental Burnout Ibu Rumah Tangga dengan Anak Autism Spectrum Disorder - Raychana, Raychana; Ayunda, Vyra Putri; Pramesti, Aprillia Dyah Ayu; Nurwahyudi, Putri; Farisandy, Ellyana Dwi (Personifikasi: Jurnal Ilmu Psikologi, 2024)
This research was conducted to reveal in depth the dynamics of parental burnout in housewives with children with Autism Spectrum Disorder (ASD). This research uses a qualitative approach with a phenomenology and interpretive paradigm. Participants in the research study were determined using purposive sampling techniques. There were two housewives with children with Autism Spectrum Disorder (ASD) and living in a nuclear family as research participants. The data collection method was carried out by means of through interviews using moderately scheduled and in-depth interviews, non-participant observation with narrative types, and documentation. The measuring tool in this research uses parental burnout theory according to Roskam et al. Then, researchers used thematic analysis techniques (Thematic Analysis) to identify, study, and report themes in the data. The research results showed that the two informants experienced parental burnout at different levels so the dynamics differed. Y with higher parental burnout showed pinching and hitting behavior towards children and clearly stated aspects of parental burnout, whereas YS only got angry and raised his voice and did not highlight aspects of parental burnout much.